ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHIKEPUTUSAN PEMBELIAN SECARA ONLINE (E-COMMERCE) (Studi Kasus pada Konsumen Shopee di Kota Banjarmasin) - Nia Satriani; Susiladewi Susiladewi; Erni Elfisah (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2019)
The form of research used in this study is descriptive method using quantitative data analysis. Quantitative research emphasizes the analysis of numerical data (numbers) processed by statistical methods. The technique of analyzing the data used by the author is factor analysis. In this research method, researchers used the perspective of the participants as a preferred picture in obtaining research results. Data collection is done by observation, interview and Questionnaire.The purpose of this study was to determine the effect of product quality, price, promotion, distribution, and process factors that influence the occurrence of trust in making online purchasing decisions and the most dominant factor by consumers on Shopee sites / applications in Banjarmasin city.The results of this study suggest that product, promotion, and distribution / place factors partially have a positive effect on trust in online purchasing decisions (case studies at Shopee Consumers in Banjarmasin City), while the price factor (price) does not have a partial effect on trust in making purchasing decisions online (case study at Shopee Consumers in Banjarmasin). The results of product (product), price (promotion), promotion (promotion), and distribution / place simultaneously have an influence on online purchasing decision making (a case study at Shopee Consumers in Banjarmasin Said). The results of this study prove that Distribution / Place is the most dominant factor influencing online purchasing decisions. Keywords: E-Commerce, Quality, Shopee.